2007
DOI: 10.1586/14779072.5.3.387
|View full text |Cite
|
Sign up to set email alerts
|

Enoxaparin in acute coronary syndromes

Abstract: Enoxaparin is a low-molecular-weight heparin (LMWH) derivative that exerts its anticoagulant activity through antithrombin III, an endogenous inhibitor of factor Xa and thrombin IIa. Unlike its unfractionated heparin (UFH) counterparts, enoxaparin has a greater bioavailability, lower incidence of heparin-induced thrombocytopenia and more stable and predictable anticoagulation, allowing fixed dosing without the need for monitoring. These advantages make it an attractive anticoagulant to be used in acute coronar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…The extent and the nature of the studies required to obtain a MAA for LMWH copies is an issue of debate [3]. Moreover, enoxaparin has consistently shown its superiority in terms of efficacy when compared to UFH and other LMWHs in the specific clinical setting of antithrombotic management of ACS [12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…The extent and the nature of the studies required to obtain a MAA for LMWH copies is an issue of debate [3]. Moreover, enoxaparin has consistently shown its superiority in terms of efficacy when compared to UFH and other LMWHs in the specific clinical setting of antithrombotic management of ACS [12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…Low molecular weight heparins (LMWHs) are a family of anticoagulants that are widely used in the treatment and the prophylaxis of venous and arterial thromboembolism. In the specific clinical setting of antithrombotic management of acute coronary syndrome (ACS), the LMWH enoxaparin has consistently shown its superiority in terms of efficacy when compared to unfractionated heparin (UFH) and other LMWHs [1][2][3]. In this clinical indication, enoxaparin is now the gold standard for anticoagulation and is extensively used in everyday practice [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Several clinical trials and meta-analyses have consistently demonstrated the efficacy of enoxaparin in reducing cardiovascular events and mortality in this population. [1][2][3][4] Studies from India show that LMWH, enoxaparin, is replacing UFH in the treatment of unstable angina. Calculation of costs incurred by patients in the treatment of a single episode of unstable angina at a tertiary care Indian hospital showed that the mean cost of treatment of a single episode of unstable angina in the hospital was US$494 (+271) against an annual per capita income of US$245.…”
Section: Introductionmentioning
confidence: 99%